Vagaries of Indian monsoon rainfall and its relation- ships with regional/global circulations - PARTHASARATHY, B.; SONTAKKE, N. A.; MUNOT, A. A.; KOTHAWALE, D. R. (MAUSAM, 1990)
Attempts have been made to understand the behaviour of the monsoon rains for which excellent data sets are available covering the period of 1871-1988. There are two discontinuities (sudden or abrupt change periods) noticed in the rainfall series in the years 1894 and 1961 and the country's rainfall series has passed through four different epochs. Three important families of circulation parameters, mainly (i) conditions over Indian region, (ii) cross equatorial flow over Indian Ocean reg1on and (iii) southern oscillation, Which are well associated with all India monsoon rainfall have been examined for the period 1951-80 and results are presented. These associations can be utilized for the prediction of the monsoon rains.